Lower secondary intended curricula of science subjects and mathematics: a comparison of the Czech Republic, Estonia, Poland and Slovenia - Kácovský, Petr; Jedličková, Tereza; Kuba, Radim; Snětinová, Marie; Surynková, Petra; Vrhel, Matěj; Urválková, Eva Stratilová (Journal of curriculum studies, 2022)
Comparative studies on science curricula provide insights into educational standards worldwide. Accordingly, in this study, we analysed the intended curricula of mathematics and science subjects of the Czech Republic, Estonia, Poland and Slovenia by comparing their lower secondary (ISCED 2) National Curriculum Documents on mathematics, physics, chemistry, biology, geography and geology from the perspective of learning outcomes. By document analysis, we extracted obligatory learning outcomes from the national curricula, assessing their level of detail and structure. A team of seven coders also measured cognitive demands of the learning outcomes using the revised Bloom's taxonomy. Our results showed considerable differences in the number of learning outcomes across countries and in the structure of these outcomes across subjects, even within national documents. Cognitive demands determined by learning outcomes were similar across the countries, but metacognitive knowledge and cognitive processes of higher level (Evaluate and Create) were mostly overlooked. We also found a lack of learning outcomes explicitly requiring the use of ICT, experimental or field work or data analysis. Although these requirements are usually formulated in general sections of curriculum documents, we recommend explicitly incorporating them into these documents as individual learning outcomes.